Politeness Principles in “Murder On The Orient Express” Film: A Pragmatic Study - Nabila, Isma; Heryono, Heri (JALL (Journal of Applied Linguistics and Literacy), 2025)
This research examines the application of the principle of politeness in the film "Murder on the Orient Express" using a pragmatic approach. This study analyzes how each dialogue spoken by the characters in the film can be defined as part of the principle of politeness maxims proposed by Geoffrey Leech. There are 6 maxims of politeness principles, namely the maxim of tact, the maxim of generosity, the maxim of agreement, the maxim of politeness, the maxim of agreement, and the maxim of sympathy. Of all these maxims, this study analyzes the order in which these maxims appear in the dialogue conversations in this film, along with possible reasons. The research method used by the author in this study is a qualitative descriptive research method that can examine evidence of the emergence of speech that implies the principles of politeness maxims in it. In this study, the author found (2) maxims of tact, (5) maxims of generosity, (9) maxims of agreement, (8) maxims of politeness, (6) maxims of agreement, and (3) maxims of sympathy. In conclusion, this study demonstrates the relevance of politeness principles in understanding communication dynamics in a fictional context, highlighting how these principles contribute to character development and plot development. Further research is recommended to explore the application of politeness principles across cultures in film and other media.